Evaluation of SIMKES at Puskesmas Kwamki Lama Mimika Using the HOT-FIT Method - Betesda Feronika Lumbanraja; Penidas Fiodinggo Tanaem (Sistemasi: Jurnal Sistem Informasi, 2023)
This research was conducted with the aim of assessing or assessing the level of success of an information system used, namely the Health Management Information System or known as SIMKES in supporting the service process at the Kwamki Lama Mimika Health Center. This information system is still relatively new in its implementation, namely since the end of September 2022 and there has not been an evaluation related to this system for the puskesmas kwamki. This research uses the Human, Organization, Technology and Net Benefit (HOT-Fit) model approach because it focuses more on several important aspects by distributing questionnaires to all employees of the puskesmas kwamki who access SIMKES directly. The results obtained from the average value of each indicator for system users 3.90 (Good), organizational structure 4.11 (Good), system quality 3.74 (Good), information quality 4.15 (Good), quality service 3.85 (Good), and benefits 4.11 (Good). So that the overall SIMKES score obtained was 3.98 (Good). Based on this, it is known that the success rate of SIMKES is good in helping the service process.